Marxist Dialectics in Bhandari’s People’s Multiparty Democracy - Chand, Hari Bahadur (State, Society and Development: PMPD Perspectives, 2026)
Madan Bhandari’s People’s Multiparty Democracy (PMPD) emerged at a crucial historical moment shaped by two interconnected developments: Nepal’s transition from active to constitutional monarchy with multiparty democracy and the global crisis of socialism following the Soviet collapse. In response, Bhandari sought to reformulate socialist transformation within a democratic framework. Although previous scholarship has explored PMPD from party centered, ideological, and praxis-oriented perspectives, its underlying dialectical logic has received limited scholarly attention. This article addresses that gap by examining PMPD as a dialectical reformulation of socialist transition theory under democratic conditions, reconstructing the theoretical framework through which Bhandari identified Nepal’s structural contradictions, envisioned a gradual process of socialist transformation, and formulated PMPD as a historically grounded synthesis. Employing qualitative textual analysis, the study applies the three classical laws of Marxist dialectics—the unity and interpenetration of opposites, the transformation of quantity into quality, and the negation of the negation—as its principal analytical framework. The analysis demonstrates that each law performs a distinct yet interconnected function within PMPD: the first illuminates Nepal’s mutually constitutive social contradictions, the second grounds a cumulative strategy of democratic mass mobilization, and the third conceptualizes PMPD as a dialectical sublation of both feudal autocracy and authoritarian socialism. These operations collectively reveal PMPD as a systematic application of materialist dialectics to Nepal’s historical conditions, contributing to creative Marxism and socialist transition theory while foregrounding a significant non-Western intervention in debates on democracy and socialist transformation.